THE EFFECT OF HYPO - OSMOLAR SOLUTIONS WITH HIBI - TANE ON SHED CANCER CELLS IN PERITONEAL CAVITY OF PATIENTS WITH GASTRIC CANCER - Dai, Dongqiu; Chen, Junqing; Yuan, Yuan; Dong, Ming; Wang, Meixian; Wang, Shubao; Qi, Chunlian; Liang, Hongwei (Chinese Journal of Cancer Research, 2013)
For 100 patients with gastric canvw, intraopemtive intraperitoneal perfusion (IOIPP) using double - distilled water(D. D. W) with hibitane 37°C for 5 mlmge$ was performed. The anticancer effects were assessed cytologically in pre- IOIPP and post-IOIPP specimens of the abdominal effusion and/or iavaged peritoneal fluid. The radical gastrectomy was performed in 65 of 93 cases with advanced gastric cancer, shed cancer cells in peritoneal cavity were detected in 16 of 65 cases with pre- IOIPP (24.62%) and in3 of post- IOIPP cases (4.62%). There was siguificant difftTmce between the two groups (P